The Revitalizing Prophetic Values in Islamic Religious Education in the Age of Technophilia at Higher Education Institutions - Ridholloh Ridholloh; Arham Muhammad Robbani (Yayasan Darusssalam Bengkulu, 2026)
This study aims to analyze the revitalization of prophetic values in Islamic Religious Education (PAI) instruction amid a trend toward technological fetishism that is, the tendency to treat technology as the central focus and measure of educational quality, thereby marginalizing relational, moral, and spiritual aspects. The study employs a qualitative approach using a single-case study design at the PAI Study Program at UIN Syarif Hidayatullah Jakarta. Data were collected through in-depth interviews, observations of learning and academic activities, and analysis of curriculum documents and instructional materials. Research informants included students, faculty members, and program administrators selected through purposive sampling. Data analysis was conducted through data condensation, data presentation, and the derivation and verification of conclusions. The findings indicate that the value of humanization is evident in lecturers’ efforts to maintain empathetic, personal, and humane learning relationships amid the demands of academic administration. The value of transcendence is evident in the awareness of muraqabah, which encourages students to maintain academic integrity, particularly in the use of AI. The value of liberation is evident in open-mindedness, social concern, freedom of association, the protection of safe spaces, and critical literacy in digital spaces.